84.5k views
5 votes
Use the graph to complete the statement. O is the origin. Ry−axis ο Ry=x: (-1,2)

A. (2, -1)
B. (-2, -1)
C. (-1, -2)
D. (1, -2)

Use the graph to complete the statement. O is the origin. Ry−axis ο Ry=x: (-1,2) A-example-1
User Widor
by
5.0k points

1 Answer

2 votes

Answer:


(x,y) = (1,2) --------
R_(y-axis)


(x,y)=(2,-1) ---------
R_(y=x)

Explanation:

Given


(x,y) = (-1,2)

Required


R_(y-axis)


R_(y=x)


R_(y-axis) implies that:


(x,y) = (-x,y)

So, we have: (-1,2) becomes


(x,y) = (1,2)


R_(y=x) implies that


(x,y) = (y,x)

So, we have: (-1,2) becomes


(x,y)=(2,-1)

User Adrien Arcuri
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.